Crystallisation behaviour and morphological studies of PEKK and carbon fibre/PEKK composites. (August 2022) - Pérez-Martín, Helena; Mackenzie, Paul; Baidak, Alex; Ó Brádaigh, Conchúr M.; Ray, Dipa
Graphical abstract: Highlights: The thermal history of PEKK and CF/PEKK impacts its crystallinity development. The inclusion of carbon fibres affects the crystallisation kinetics of PEKK. PEKK undergoes a dual crystallisation mechanism depending on the thermal cycle. Crystallisation kinetics models are successfully implemented on PEKK and CF/PEKK. Abstract: The increased interest in carbon fibre/poly(etherketoneketone) (CF/PEKK) as an option for high-performance applications calls for a thorough understanding of the composite's crystallisation behaviour, due to the essential role that crystallinity plays in performance. In this study, differential scanning calorimetry was used with a variety of thermal cycles to evaluate the effect of thermal history on crystallinity development in unreinforced PEKK and CF/PEKK. Different isothermal holding temperatures during cooling affected the ratio between primary and secondary crystallisation, and non-isothermal cooling cycles influenced the extent of crystallisation. The inclusion of carbon fibres increased the proportion of secondary crystallisation in the matrix and slowed down crystallisation kinetics. A Velisaris-Seferis model was used to model crystallisation kinetics for the isothermal data, and adapted Nakamura models were used for the non-isothermal data. Based on this work, optimum isothermal hold temperatures during cooling for CF/PEKK are estimated to lie in the range of 220–260 °C.